Early dynamics of T helper cell cytokines and T regulatory cells in response to treatment of active Mycobacterium tuberculosis infection. (March 2015) - Feruglio, S. L.; Tonby, K.; Kvale, D.; Dyrhol‐Riise, A. M.
Summary Biomarkers that can identify tuberculosis (TB) disease and serve as markers for efficient therapy are requested. We have studied T cell cytokine production [interferon (IFN)‐γ, interleukin (IL)‐2, tumour necrosis factor (TNF)‐α] and degranulation (CD107a) as well as subsets of CD4+ T regulatory cells (Tregs) after in‐vitro Mycobacterium tuberculosis (Mtb) antigen stimulation [early secretory antigenic target (ESAT)‐6, culture filtrate protein (CFP)‐10, antigen 85 (Ag85)] in 32 patients with active tuberculosis (TB) disease throughout 24 weeks of effective TB treatment. A significant decline in the fraction of Mtb‐specific total IFN‐γ and single IFN‐γ‐producing T cells was already observed after 2 weeks of treatment, whereas the pool of single IL‐2+ cells increased over time for both CD4+ and CD8+ T cells. The Treg subsets CD25highCD127low, CD25highCD147++ and CD25highCD127lowCD161+ expanded significantly after Mtb antigen stimulation in vitro at all time‐points, whereas the CD25highCD127lowCD39+ Tregs remained unchanged. The fraction of CD25highCD127low Tregs increased after 8 weeks of treatment. Thus, we revealed an opposing shift of Tregs and intracellular cytokine production during treatment. This may indicate that functional signatures of the CD4+ and CD8+ T cells can serve as immunological correlates of early curative host responses. Whether such signatures can be used as biomarkers in monitoring and follow‐up of TB treatment needs to be explored further.